COMPARISON AND CORRELATION OF PHYSICAL PROPERTIES FROM THE PLAIN AND SLOPE SEDIMENTS IN THE ULLEUNG BASIN, EAST SEA (SEA OF JAPAN) - Kim G.Y.; Kim D.C. (My University, 2001)
High-resolution profiles (chirp sonar, 2-7kHz) acquired from the Ulleung Basin, East Sea (Sea of Japan) revealed several discrete echo types, suggesting deposits formed mainly by mass flow processes. The Ulleung Basin plain sediments are characterized by turbidite/hemipelagic deposits, while slide, slump, and debrite deposits are mainly found in the slope area. Rock fall deposits also appear near the Ulleung Island. The core sediments show distinctive downslope variations in most physical properties studied. Over the plain and the slope, mass physical properties (water content, porosity, wet bulk density, shear strength, and velocity) show considerably different values in spite of the nearly constant sediment texture. However, the relationships among the physical properties have relatively good correlations, although the absolute values are different. Grain density in the plain is relatively lower than the slope, probably because of a tephra and calcite compensation depth (CCD). Therefore, we suggest that the slope sediments may be affected by sedimentological changes resulting from diagenesis such as a certain degree of compaction and/or consolidation.
Keywords: EAST SEA; ULLEUNG BASIN; CHIRP SONAR PROFILES; MASS PHYSICAL PROPERTIES